Advances in diagnosing mild cognitive impairment and Alzheimer’s disease using 11C-PIB- PET/CT and common neuropsychological tests - Zhao, Qing; Du, Xinxin; Chen, Wenhong; Zhang, Ting; Xu, Zhuo (Frontiers in Neuroscience, 2023)
Alzheimer’s disease (AD) is a critical health issue worldwide that has a negative impact on patients’ quality of life, as well as on caregivers, society, and the environment. Positron emission tomography (PET)/computed tomography (CT) and neuropsychological scales can be used to identify AD and mild cognitive impairment (MCI) early, provide a differential diagnosis, and offer early therapies to impede the course of the illness. However, there are few reports of large-scale 11C-PIB-PET/CT investigations that focus on the pathology of AD and MCI. Therefore, further research is needed to determine how neuropsychological test scales and PET/CT measurements of disease progression interact.